2014
DOI: 10.1111/jdv.12453
|View full text |Cite
|
Sign up to set email alerts
|

Changes in nuclear morphology and chromatin texture of basal keratinocytes in melasma

Abstract: Basal keratinocytes from facial melasma display changes in nuclear form and chromatin texture, suggesting that the phenotype differences between melasma and adjacent facial skin can result from complete epidermal melanin unit alterations, not just hypertrophic melanocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 16 publications
(20 reference statements)
1
16
0
1
Order By: Relevance
“…Regarding the areas of photoexposed skin in melasma‐affected patients, different phenotypic expressions in the epidermal‐melanin unit were observed that superimposed in an intriguing way, suggesting the possibility of mosaic‐like focal changes . Factors involved in its development most likely act directly on melanogenesis and on the cytocrine activity of melanosomes, rather than a systemic change in which generalized pigmentation would be expected, such as that induced by ACTH administration in patients .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the areas of photoexposed skin in melasma‐affected patients, different phenotypic expressions in the epidermal‐melanin unit were observed that superimposed in an intriguing way, suggesting the possibility of mosaic‐like focal changes . Factors involved in its development most likely act directly on melanogenesis and on the cytocrine activity of melanosomes, rather than a systemic change in which generalized pigmentation would be expected, such as that induced by ACTH administration in patients .…”
Section: Discussionmentioning
confidence: 99%
“…Melanocytes from melasma‐affected skin are locally hyperfunctioning due to specific paracrine stimulus from melanogenic substances secreted by neighbour keratinocytes, influenced by environmental factors, such as ultraviolet radiation and sex steroid hormones .…”
Section: Discussionmentioning
confidence: 99%
“…Hingga saat ini patogenesisnya belum dapat dijelaskan sepenuhnya. [1][2][3] Belum banyak pula penelitian tentang karakter pewarisan genetik pada melasma yang berhubungan dengan warna kulit. [4][5][6][7] Warna kulit manusia ditentukan oleh jenis pigmen eumelanin dan pheomelanin yang diregulasi oleh gen melanocortin-1 receptor (MC1R) dan agouti signaling protein (ASIP), serta dipengaruhi oleh letak geografis tempat seseorang tersebut berasal.…”
Section: Pendahuluanunclassified
“…It is mainly associated with sun exposure and sex steroids (pregnancy and oral contraceptives), with frequent family involvement (40-60%). 1-3 …”
Section: Introductionmentioning
confidence: 99%